Intonology - An Independent Field of Linguistics - Gulchehra Toshpulat qizi Cholliyeva (Researchparks Publishing, 2021)
The article deals with intonology, one of the youngest branches of linguistics. It has been studied in world linguistics since the emergence of ontonology as an independent field, and the scholars who contributed to it have been mentioned. Information is provided on the components, units and role of this field in Uzbek linguistics. Unity of intonology The function of intonation in the speech process is studied.